Pengaruh Kepemimpinan, Disiplin Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Dinas Sosial Kabupaten Bojonegoro - Elsa Syafira Yuniarensia; Shinta Setia (Universitas Batanghari Jambi, 2023)
This study aims to examine the influence of Leadership, Work Discipline and Work Environment on the Performance of Social Service Employees in Bojonegoro Regency. The sample of this study were 51 respondents, all employees of the Bojonegoro Regency Social Service, with a minimum working period of more than one year. sampling technique using Purposive Sampling. The analysis of this study used Structural Equating Modeling (SEM) on Wrap Partial Least Square (PLS) version 8.0 and data collection techniques in the form of questionnaires which were distributed directly. The results of this study indicate that leadership has a positive and significant effect on employee performance, work discipline has no significant effect on employee performance and the work environment has a negative and insignificant effect on employee performance.